Pengaruh LKPD Berbasis Inkuiri Terbimbing Terhadap Penguasaan Konsep Biologi Peserta Didik Pada Materi Genetika - Nursal Marleni (Indonesian Publication Center, 2020)
Learning based on 21st century skills is a major need in an era based on innovation and creativity. One form of skills needed, especially in experimental-based learning forms such as biology, is the skill to master the concept of what will be studied by students. Therefore, the purpose of this study was to determine the effect of using student worksheets based on guided inquiry models on the mastery of the concept of special students on genetic material. This research is a classroom action research, and focuses on a special cycle for the use of LKPD during biology lab work for genetic material. The sample was selected using the cluster random method and obtained 60 students of class XII IPA. Data analysis used N-gain analysis to determine the increase in students' skills in solving problems related to genetic material for Mendelian crosses. The results showed that there was an increase in the students' mastery of concepts. Students' mastery of concepts increases after learning to use guided inquiry based LKPD.